Carnivores in ecosystems : the Yellowstone experience - Clark, Tim W. (Yale University Press, 1999)
"Large carnivores - such as the gray wolf and grizzly bear - are in danger of extinction; saving them is one of the most difficult challenges facing conservation biologists worldwide. Other carnivores - such as the mountain lion, wolverine, and lynx - are in need of special management. This valuable book examines the current status, management, and conservation of carnivores in the Greater Yellowstone Ecosystem, where these animals have not only been researched for almost forty years but have also been affected by pressures from growing human uses."--Jacket